Molecular Diagnosis of Babesia gibsoni Infection - Chandra, B. Subhash; Rajkumar, K.; Thanislass, J.; Vijayalakshmi , P.; Prabavathy, A. Abiramy (International Journal of Livestock Research, 2018)
In the present investigation, sixty-eight blood samples collected from the dogs suspected for Babesia gibsoni infection were subjected for examination of sensitivity of PCR in diagnosis of the disease. The present study was carried out at Rajiv Gandhi Institute of Veterinary Education and Research, Puducherry. Dogs presented to the Small Animal Unit, Teaching Veterinary Clinical Campus were taken for the study. Dogs suspected for Babesia gibsoni infection were subjected for diagnosis using Giemsa stained blood smear examination and Polymerase Chain Reaction. Samples turned out positive were custom sequenced and analyzed. More number of samples were found to be positive for babesiosis by Polymerase chain reaction. Isolate identified was found to be Babesia gibsoni (Asian Genotype). Polymerase chain reaction was superior to blood smear examination in diagnosing babesiosis and the incidence of disease was significantly higher in young age group.